2019
DOI: 10.1016/j.apenergy.2019.03.179
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on hydrogen hydrate with tetrahydrofuran by differential scanning calorimeter and in-situ Raman

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Calorimetry techniques are essential for investigating the thermodynamic properties of hydrates and obtaining phase equilibrium data (Sum et al, 2009). A huge number of articles can be found in the literature concerning the use of DSC and -DSC techniques applied to gas hydrates, such as the study of hydrate nucleation (Davies et al, 2009), effect of additives (Daraboina et al, 2011), cold storage in air-conditioning systems (Li et al, 2010), gas separation (Zhong et al, 2018), and hydrogen storage (Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Calorimetry techniques are essential for investigating the thermodynamic properties of hydrates and obtaining phase equilibrium data (Sum et al, 2009). A huge number of articles can be found in the literature concerning the use of DSC and -DSC techniques applied to gas hydrates, such as the study of hydrate nucleation (Davies et al, 2009), effect of additives (Daraboina et al, 2011), cold storage in air-conditioning systems (Li et al, 2010), gas separation (Zhong et al, 2018), and hydrogen storage (Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al. ( Cai et al, 2019 ) and Veluswamy et al. ( Veluswamy and Linga, 2013 ) studied the effect of simultaneous change in temperature and pressure in a system with THF promotor.…”
Section: Hydrogen Hydratementioning
confidence: 99%
“…Cai et al. ( Cai et al, 2019 ) compared the hydrate dissociation process in hydrate systems prepared in fresh water and memory water. The results indicated that memory effect has no significant influence on thermal state of hydrate.…”
Section: Hydrogen Hydratementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, high pressures are needed to form pure hydrogen hydrates, which is not economically feasible and leads to the research of the mixed hydrogen hydrates at lower pressures [28][29][30][31][32][33]. For example, Florusse et al [34] suggested that tetrahydrofuran can stabilize the hydrogen hydrates at 5.0 MPa and 279.6 K, and Lee's group [7] reported that the storage capacity is about 4.0 wt% at 12 MPa for the binary hydrogen hydrate.…”
Section: Introductionmentioning
confidence: 99%